Patterns of Behavior in Police and Citizen Transactions: Boston, Chicago, and Washington, DC, 1966 - Reiss, Albert J. Jr ([Verlag nicht ermittelbar], 1989)
These data have been influential in the development of theories of police behavior. Variables in the collection supply information on the nature and context of encounters between citizens and the police. Data are included on the characteristics and roles of individuals involved in an encounter, relationships among the participants in the encounter, individuals' definitions of the situation after the arrival of police, specific police actions and manner of police behavior during the encounter, and informal characterizations by police of participants involved in the encounter. In cases where offender suspects were involved, information was collected on restraints employed, searches, interrogations, confessions, advisement of rights, booking, and other arrest processes.